Characterization of Ag-promoted Ni/SiO2 Catalysts for Syngas Production via Carbon Dioxide (CO2) Dry Reforming of Glycerol - Norazimah, Harun; Jolius, Gimbun; Mohammad Tazli, Azizan; Sumaiya, Zainal Abidin (Department of Chemical Engineering, Diponegoro University, 2016)
The carbon dioxide (CO2) dry reforming of glycerol for syngas production is one of the promising ways to benefit the oversupply crisis of glycerol worldwide. It is an attractive process as it converts carbon dioxide, a greenhouse gas into a synthesis gas and simultaneously removed from the carbon biosphere cycle. In this study, the glycerol dry reforming was carried out using Silver (Ag) promoted Nickel (Ni) based catalysts supported on silicon oxide (SiO2). The catalysts were prepared through wet impregnation method and characterized by using Bruanaer-Emmett-Teller (BET) surface area, Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), and Thermo Gravimetric (TGA) analysis. The experiment was conducted in a tubular reactor which condition fixed at 973 K and CO2: glycerol ratio of 1, under atmospheric pressure. It was found that the main gaseous products are H₂, CO and CH4 with H₂:CO < 1.0. From the reaction study, Ag(5)NiSiO2 results in highest glycerol conversion and hydrogen yield, accounted for 32.6% and 27.4%, respectively.